2022
DOI: 10.3389/fphys.2022.898251
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Relative Bradycardia and Relative Tachycardia in Individuals Diagnosed With COVID-19

Abstract: The COVID-19 disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has become one of the worst global pandemics of the century. Wearable devices are well suited for continuously measuring heart rate. Here we show that the Resting Heart Rate is modified for several weeks following a COVID-19 infection. The Resting Heart Rate shows 3 phases: 1) elevated during symptom onset, with average peak increases relative to the baseline of 1.8% (3.4%) for females (males), 2) decrease thereafte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 57 publications
1
15
1
Order By: Relevance
“…7 , 34 Natarajan et.al found RMSSD exhibits a similar three-stage temporal evolution as RHR, except that the phase is reversed, that is, when RHR increases, RMSSD decreases and vice versa. 22 However, contrary to previous research, we found no dynamic changes in HRV with the progression and exacerbation of the disease. This may be due to the less severe patients and shorter observation periods in this outbreak.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…7 , 34 Natarajan et.al found RMSSD exhibits a similar three-stage temporal evolution as RHR, except that the phase is reversed, that is, when RHR increases, RMSSD decreases and vice versa. 22 However, contrary to previous research, we found no dynamic changes in HRV with the progression and exacerbation of the disease. This may be due to the less severe patients and shorter observation periods in this outbreak.…”
Section: Discussioncontrasting
confidence: 99%
“… 19 Natarajan et al showed that patients’ heart rates increased abnormally around the time of onset, began to decrease 1 week after onset, and returned to baseline around the 21st day after onset. 5 In their later study of long COVID, 22 they observed that RHR (the average heart rate during sleep) undergoes three distinct phases: (a) a rise during the onset of symptoms with an average peak increase relative to baseline, (b) a subsequent decline, reaching a minimum approximately 13 days after symptom onset, and (c) a subsequent increase, culminating in a second peak around 28 days after symptom onset, returning to baseline levels on average about 112 days after symptom onset. Similar changes were seen in the study by Radin et al 23 In our study, we observed a significant decrease in RHR and sleep heart rate in the more severe group at day 25 after onset, similar to the third stage of RHR change found by Natarajan et al Probably because our sample size was small and our observation period was not long enough, the pattern of RHR changes found by Natarajan et al was not fully represented in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As has previously been reported [20,21], we observe a pattern of transient RHR elevation from COVID-19 infection onset for a week, followed by a period of transient reduced RHR from the second to third week, and finally a chronic or long-lasting increase in resting heart rate in some participants which can last several months or longer (Figure 4. This pattern of acute elevation and subsequent reduction is more prominent in the LCOVID cohort compared to the short COVID cohort, as shown in Figure 4.…”
Section: Discussionsupporting
confidence: 84%
“…Studies utilizing data from fitbit devices have shown modification in the Resting Heart Rate (RHR) for up to 3 months following symptom onset with substantial intraindividual variability. A pattern of bradycardia and tachycardia in the RHR were also observed in the patients over this period ( 17 , 18 ). For patients with underlying heart conditions and respiratory disease, COVID-19 can have fatal consequences.…”
Section: Introductionmentioning
confidence: 52%